2020
DOI: 10.1177/0271678x20908355
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective role of lactate in rat neonatal hypoxia-ischemia

Abstract: Hypoxic-ischemic (HI) encephalopathy remains a major cause of perinatal mortality and chronic disability in newborns worldwide (1–6 for 1000 births). The only current clinical treatment is hypothermia, which is efficient for less than 60% of babies. Mainly considered as a waste product in the past, lactate, in addition to glucose, is increasingly admitted as a supplementary fuel for neurons and, more recently, as a signaling molecule in the brain. Our aim was to investigate the neuroprotective effect of lactat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 81 publications
(121 reference statements)
2
58
0
1
Order By: Relevance
“…In adults with traumatic brain injury, administration of 13 C-labeled lactate via the microdialysis catheter and simultaneous collection of the microdialysates, with 13 C NMR analysis, revealed 13 C labeling in glutamine, consistent with lactate metabolism in the TCA cycle ( 31 , 35 ). Interestingly, Roumes et al ( 36 ) recently demonstrated the neuroprotective effect of exogenous lactate administration in a neonatal HI rat model. Rice-Vannucci P7 rats that received intraperitoneal injection of lactate following unilateral carotid ligation exhibited a significant reduction in the volume of high-signal intensity brain lesions on DWI and reduced severity of cytotoxic edema as demonstrated by higher apparent diffusion coefficient (ADC) values compared to animals that received 0.9% sodium chloride.…”
Section: Discussionmentioning
confidence: 99%
“…In adults with traumatic brain injury, administration of 13 C-labeled lactate via the microdialysis catheter and simultaneous collection of the microdialysates, with 13 C NMR analysis, revealed 13 C labeling in glutamine, consistent with lactate metabolism in the TCA cycle ( 31 , 35 ). Interestingly, Roumes et al ( 36 ) recently demonstrated the neuroprotective effect of exogenous lactate administration in a neonatal HI rat model. Rice-Vannucci P7 rats that received intraperitoneal injection of lactate following unilateral carotid ligation exhibited a significant reduction in the volume of high-signal intensity brain lesions on DWI and reduced severity of cytotoxic edema as demonstrated by higher apparent diffusion coefficient (ADC) values compared to animals that received 0.9% sodium chloride.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the lactate level rises after a hypoxic-ischemic episode 22,23 . It is likely that administration of lactate could further leverage the effect of HCAR1: two recent studies showed that mouse pups injected with lactate before, or in the hours or days following HI had improved recovery 7,8 . The authors suggested that the protective effect of lactate was mainly due to lactate being used as a metabolite to make ATP 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that administration of lactate could further leverage the effect of HCAR1: two recent studies showed that mouse pups injected with lactate before, or in the hours or days following HI had improved recovery 7,8 . The authors suggested that the protective effect of lactate was mainly due to lactate being used as a metabolite to make ATP 7,8 . However, our data suggest that recovery after lactate injection is partly mediated by HCAR1, which promotes a stronger transcriptional response to HI and thereby facilitates neurogenesis and tissue regeneration after injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…donc du potentiel d'oxydo-réduction de la cellule, qui contrôle de nombreuses réactions enzymatiques. L'administration de lactate est déjà testée en clinique comme thérapie après un traumatisme crânien chez l'adulte [19] [18]. Un suivi longitudinal de ces animaux, à la fois par IRM, pour déterminer la…”
Section: Astrocyte-neurone : Un Couple Métabolique Soudéunclassified